From psychoanalytic bisexuality to bisexual psychoanalysis : desiring in the real - Rapoport, Esther (Abingdon, Oxon ; New York, NY : Routledge, 2020)
This is the first book to assess bisexuality through a range of psychoanalytic and critical perspectives, highlighting both the issues faced by bisexual people in contemporary society and the challenges that can be presented by bisexual clients within a clinical setting. Examining bisexuality through the lenses of Lacanian, Winnicottian and Relational psychoanalytic theories, the book outlines the ways in which the concept is at once both dated and yet still tremendously important. It includes case studies to explore the issue of widespread countertransference responses in the clinical setting, in addition to using both bisexual theory and empirical research on biphobia to comment on the social pressures facing bisexual men and women, and the resultant psychological effects. Bisexual identities and practices have become increasingly visible in recent years, and this important book addresses the lack of critical reckoning with the topic within the psychoanalytic community. It will be of great interest to practicing psychoanalysts and psychotherapists as well as to researchers across the fields of psychoanalysis and genderand sexuality studies.
Introduction -- Bisexuality: the undead (m)other of psychoanalysis -- Which traditional psychoanalytic meanings of bisexuality are worth keeping, and which -- Had better go? -- Object choice: choosing objects of psychoanalytic inquiry from among the different meanings of bisexuality -- Bisexual subjectivity through the lenses of Lacanian, object relations and relational theories -- Epistemologies of the fence: meeting points between bisexual and contemporary psychoanalytic epistemologies -- Bisexuality and oedipus, a strained relationship: anti-Oedipal, post-Oedipal, and extra-Oedipal bisexualities -- Abjection in action: bisexual patient and transference-countertransference dynamics -- Women and men: overlapping experiences, different pressures -- Masters of transformation: bisexual and transgender bodies and the problem of death.
OCLC-licensed vendor bibliographic record.
Keywords: Bisexuality -- Psychological aspects; Psychoanalysis; FAMILY & RELATIONSHIPS / Life Stages / General; PSYCHOLOGY / Developmental / General; PSYCHOLOGY / Developmental / Lifespan Development; PSYCHOLOGY / General; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health